The effect of cytokine adsorption on leukocyte and platelet activation after extracorporeal cardiopulmonary resuscitation - Zahn, Timm; Schanze, Nancy; Staudacher, Dawid L.; Wengenmayer, Tobias; Maier, Sven; Benk, Christoph; Gauchel, Nadine; Dürschmied, Daniel; Supady, Alexander (Thrombosis and haemostasis, 2024)
Background: Post-cardiac arrest syndrome (PCAS) is a frequent complication following successful cardiopulmonary resuscitation and correlates with poor outcome. PCAS is characterized by an excessive inflammatory response to whole-body ischemia and reperfusion. Cytokine adsorption was suggested as an adjunctive treatment option for the removal of cytokines from the patients' blood to restore the physiological equilibrium of pro- and anti-inflammatory activity and thus mitigate hemodynamic instability and end-organ complications. Material and Methods: To better understand the cellular effects of cytokine adsorption in patients receiving extracorporeal cardiopulmonary resuscitation (ECPR) after in- and out-of-hospital cardiac arrest, we compared the activation status of neutrophils, monocytes, and platelets as well as the formation of platelet-leukocyte complexes in intravenous whole blood samples from an exploratory subgroup (n = 24) from the randomized CYTER study. Result: At 48 hours after initiation of ECPR, flow cytometry analyses did neither reveal significant differences in neutrophil (CD11b, CD66b, L-selectin, and PSGL-1) and monocyte (CD11b, L-selectin, and PSGL-1) surface molecule expression nor in circulating platelet-monocyte complexes between patients receiving cytokine adsorption and those without. Conclusion: Data did not show a relevant effect of cytokine adsorption on neutrophil and monocyte activation during the first 48 hours after initiation of ECPR.
Gesehen am 26.02.2024